Unsettling India Affect, Temporality, Transnationality - Mankekar, Purnima, 1961- (Book collections on Project MUSE., 2015)
Mankekar offers a new understanding of the affective and temporal dimensions of how India and "Indianness," as objects of knowledge production and mediation, circulate through transnational public cultures.